2014
DOI: 10.1177/0194599814545771
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone's Effect in the Retrocochlear Auditory Centers of a Noise‐Induced Hearing Loss Mouse Model

Abstract: Our NIHL mouse model demonstrated dose-dependent Dex pretreatment otoprotection against NIHL with preservation of retrocochlear auditory neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
(80 reference statements)
0
7
0
1
Order By: Relevance
“…44 The dexamethasone could attenuate noise-induced HL by reducing outer hair cell death and other glucocorticoid receptor-mediated effects in the cochlea. 45 Our analysis has several limitations. First, because of the limited data for participant characteristics and study designs, meta-regression analysis was not possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 The dexamethasone could attenuate noise-induced HL by reducing outer hair cell death and other glucocorticoid receptor-mediated effects in the cochlea. 45 Our analysis has several limitations. First, because of the limited data for participant characteristics and study designs, meta-regression analysis was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…44 The dexamethasone could attenuate noise-induced HL by reducing outer hair cell death and other glucocorticoid receptor–mediated effects in the cochlea. 45…”
Section: Discussionmentioning
confidence: 99%
“…IT DEX administration causes a dose-dependent preservation of retrocochlear auditory neurons in an NIHL mouse model. 22 Glucocorticoids can be used as a primary initial treatment or as a salvage therapy for SSNHL, but the clinical therapeutic outcomes of IT steroid treatments are associated with the application timing, dosage, and administration protocol. 23,24 Regardless, the key factor is delivery of a sufficient DEX concentration to the perilymph.…”
Section: Discussionmentioning
confidence: 99%
“…Heinrich et al showed that a pretreatment with DEX could prevent noise‐induced glucocorticoid receptor degradation in the lateral wall of the cochlea, implying that DEX plays a role in receptor protein turnover and restoration. However, animal studies using IT DEX treatment for NIHL have shown inconsistent results, possibly reflecting differences in the degree of acoustic trauma sustained in each animal model, the applied dose, and the duration of the DEX administration.…”
Section: Discussionmentioning
confidence: 99%
“…DXM'nin işitme kayıplarında koruyucu ve tedavi edici etkileri daha önceki çalışmalarda gösterilmiştir. 12,13 Bunun yanı sıra farklı maddelerin; N-asetilsistein, koenzim Q, E vitamini, C vitamini, A vitamini, magnezyum, idebenon, çörek otu yağı gibi antioksidanların akustik travma üzerine etkileri ile ilgili farklı çalışmalar mevcuttur. [14][15][16][17] Üzümün (Vitis vinifera) tıbbi ve besinsel değeri binlerce yıldır bilinmektedir.…”
unclassified